Humanities and Environmental Ethics: Bridging Cultural Studies and Sustainability - แก้วเกตุพงษ์, ประภาส (Journal of Exploration in Interdisciplinary Methodologies (JEIM), 2024)
This paper explores the vital role of the humanities in shaping environmental ethics and sustainability practices. By examining the contributions of literature, visual arts, philosophy, and cultural studies, the paper highlights how these disciplines provide ethical frameworks and cultural insights that are essential for fostering sustainable relationships with the environment. The paper also discusses the challenges of integrating ethical theories with practical sustainability efforts and emphasizes the opportunities for interdisciplinary collaboration between humanities scholars, environmental scientists, and policymakers. The integration of cultural heritage and diverse perspectives into global sustainability initiatives is presented as a crucial pathway for addressing the complex environmental challenges of our time.